Transformer‐Level Modeling of Geomagnetically Induced Currents in New Zealand's South Island. Issue 6 (20th June 2018) - Divett, T.; Richardson, G. S.; Beggan, C. D.; Rodger, C. J.; Boteler, D. H.; Ingham, M.; Mac Manus, D. H.; Thomson, A. W. P.; Dalzell, M.
Abstract: During space weather events, geomagnetically induced currents (GICs) can be induced in high‐voltage transmission networks, damaging individual transformers within substations. A common approach to modeling a transmission network has been to assume that every substation can be represented by a single resistance to Earth. We have extended that model by building a transformer‐level network representation of New Zealand's South Island transmission network. We represent every transformer winding at each earthed substation in the network by its known direct current resistance. Using this network representation significantly changes the GIC hazard assessment, compared to assessments based on the earlier assumption. Further, we have calculated the GIC flowing through a single phase of every individual transformer winding in the network. These transformer‐level GIC calculations show variation in GICs between transformers within a substation due to transformer characteristics and connections. The transformer‐level GIC calculations alter the hazard assessment by up to an order of magnitude in some places. In most cases the calculated GIC variations match measured variations in GIC flowing through the same transformers. This comparison with an extensive set of observations demonstrates the importance of transformer‐level GIC calculations in models used for hazard assessment. Key Points: We develop a transformer‐level network representation of New Zealand's South Island electrical transmission network to examine GIC Modeling GIC at the transformer‐level can significantly alter the perception of the GIC hazard compared to simpler substation‐level modeling We found reasonable agreement between extensive measurements of GIC and modeled transformer‐level GIC across multiple storms